The text of Marcion's gospel - Roth, Dieter T. (New testament tools, studies and documents, 2015)
Dieter T. Roth offers a new, critical reconstruction of Marcion's Gospel including various levels of certainty for readings in this Gospel text. An extensive history of research, overview of both attested and unattested verses in the various sources, and methodological considerations related, in particular, to understanding the citation customs of the sources set the stage for a comprehensive analysis of all relevant data concerning Marcion's Gospel. On the basis of this new reconstruction significant issues in the study of early Christianity, including the relationship between Marcion's Gospel and Luke and the place of Marcion in the history of the canon and the formation of the fourfold Gospel, can be considered anew